ORIENTASI POLITIK HUKUM DALAM UNDANG-UNDANG NOMOR 25 TAHUN 2007 TENTANG PENANAMAN MODAL BERDASARKAN PANCASILA - Heriyono, Heriyono (Universitas Islam Negeri Raden Fatah Palembang, 2019)
In the global era, the world has become a limit or there are no clear boundaries between countries in the world. Unstoppable globalization, which are characterized by technological developments and modernization. Its makes the distance between countries closer and growing without dividing. The impact of globalization one of which is the free market ideology or economic realization and the diminishing role of the state. Liberalization in the economic field, most in the investment sector provides access to natural resources in Indo-nesia, which is related to the Investment Law, which is then rationalized based on government regulations, ministerial regulations, and by using slogans to carry out bureaucratic reform, fair assistance to all business, and open investment. This contradicts the Indonesian Constitution. Basically, the involvement of the state government in the administration of the state, specifically in realizing the Panca-sila economy, is basically a form of state intervention in national economic activities. To convert to the Investment Law, the establishment of the Investment Law in Indonesia must be approved when setting the country as the manager of Indonesia’s natural wealth, with the aim of providing wealth and prosperity to the country. The legal political orientation of the making of the Investment Law must win the Pancasila as the nation’s law, which manages it to be inseparable from the state’s social responsibility to prosper its citizens, provide regulation in the 1945 Constitution of the Republic of Indonesia.